2022
DOI: 10.2196/35028
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Preparedness Among Older Adults With Chronic Illness: Survey of Primary Care Patients

Abstract: Background Older adults are a high priority for telemedicine given their elevated COVID-19 risk and need for frequent provider contact to manage chronic illnesses. It seems that many older adults now use smartphones but few studies have examined their overall readiness for telemedicine. Objective The aim of this study is to survey older primary care patients about their telemedicine preparedness, including internet usage, internet-capable devices, telem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…We showed that special attention should be placed on people living alone, with preexisting comorbidities or of old age. The same vulnerable groups have been identified in studies in the field of telehealth ( 18 20 , 24 , 65 , 68 ). In line with our results, continuity of staff and a trusted relationship with the telehealth provider have been identified as important to patients ( 18 ).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…We showed that special attention should be placed on people living alone, with preexisting comorbidities or of old age. The same vulnerable groups have been identified in studies in the field of telehealth ( 18 20 , 24 , 65 , 68 ). In line with our results, continuity of staff and a trusted relationship with the telehealth provider have been identified as important to patients ( 18 ).…”
Section: Discussionmentioning
confidence: 59%
“…Severe courses of disease, leading to hospitalization (VS62), but also the unexpected intensity and duration of common symptoms such as pain (VS63-64), fever (VS62), cough (VS65) and especially weakness (VS60, 66-67) impaired the participants' illness experience. The unpredictability of COVID-19, with sudden changes in symptoms and severity and the undulating recovery process was perceived difficult (VS63, [68][69].…”
Section: Illness Experience-qualitative Survey Resultsmentioning
confidence: 99%
“…The authors also note that not all populations have smartphones capable of running mobile apps. This may be especially true of older, low-income adults who only use a limited number of programs on their smartphones [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 10 articles, 1 was excluded because it did not have access to full text, leaving 9. The reverse search procedure of the references cited obtained a further 9 eligible articles, resulting in a final total of 18 papers included in the definitive analysis [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] (see Figure 1).…”
Section: Characteristic Of the Studies Includedmentioning
confidence: 99%
“…Ufholz et al [33] reported that older patients showed less use of telemedicine (23%) despite near to 80% having access to technology.…”
Section: Telemedicine Consult Perceptionmentioning
confidence: 99%